Synthesis of (±)-Pterocarpin and Its Thia- and Aza-Analogues in a Modular Manner - Huang, Qingyun; Wang, Peng; Tian, Yu; Song, Ni; Ren, Sumei; Tao, Jiaxin; Hang, Kaini; Li, Ming (Synlett, 2015)
Syntheses of racemic pterocarpin, its thia- and aza-pterocarpin have been achieved in a modular manner using sesamol iodide, diethyl malonate and 3-methoxyphenol, 3-methoxythiophenol and N-tosyl-3-methoxyaniline as building blocks. Copper-mediated Hurtley coupling, Mitsunobu reaction, IBX-mediated oxidation, Pinnick oxidation, and intramolecular Friedel–Crafts acylation have been successfully exploited in the synthesis.
Keywords: pterocarpin synthesis; thia-pterocarpin synthesis; aza-pterocarpin synthesis; pterocarpan synthesis; isoflavanone synthesis